ANALISIS RE-EVALUASI INVESTASI AKTIVA TETAP DITINJAU DARI ASPEK FINANSIAL (Studi Pada UD. UTAMA DENPASAR) - Anak Agung Ngurah Gede Suindrawan; Dewa Gede Agung Joni Sudiarta (Forum Manajemen STIMI Handayani Denpasar, 2013)
Invesment is cultivation of certain fund in number at the moment to getresult of larger ones a period of/to to come. In general invesment can be differentiatedof real invesment and invesment of ﬁ nansial. Real invesment most commonlyhappened at traditional economics, where this invesment include;cover real assetlike land;ground, building, other physical matter or machine. Whereas invesmentof ﬁ nansial in modern economics which entangle contract - contract written, likecommerce of obligation and share Intention of this research is to know competent or plant asset invesment do not whichhave been UD. Utama which evaluated from Its aspect of him.From result of analysis, hence can be concluded to following : Period Payback ( PP) obtained by 1 year 7 months 28 day meaning the the invesment competent tobe continued, because waktu yang needed to to close again expenditure of shorterinvesment of economic age of plant asset invesment, that is 8 year. Net Present Value( NVP) obtained is positive of Rp. 446.314.013 meaning yielded acceptance that isis positive, invesment bigger than invesment early, so that looked into invesment[done/conducted] by UD. Utama to be continued. Proﬁ tability Index ( PI) obtainedresult of equal to Rp. 2,3 bigger than one. This matter [of] menunjukan each;everyinvested rupiah will be obtained by earnings equal to Rp. 2,3. Thereby invesment[done/conducted] by UD. Utama to be continued is. Internal [of] Rate Of Returnobtained by result 61,6 % which bigger than expense of or capital of cost capitaof! accounted by is company equal to 18%. so that invesment by UD. Utama to becontinued. Pursuant to conclusion above plant asset invesment is .UD. Utama which evaluated from aspect of ﬁ nansial competent to in to continuing.